2016
DOI: 10.1016/j.poly.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

BDI∗MgX(L) where X = Bu and O Bu and L = THF, py and DMAP. The rates of kinetic exchange of L where BDI∗= CH{C( Bu)N-2,6- Pr2C6H3}2

Abstract: a b s t r a c t BDI * Mg n Bu(THF) and rac-LA to produce heterotactic PLA have been shown to increase from P r = 0.5-0.65 from DCM to neat THF. The increase in concentration of THF from M THF = 0 in toluene to neat THF is shown to occur by THF dissociation as deduced by 1 H NMR studies. In related systems where X = n Bu and O t Bu and with ligands L = THF, py and DMAP similar processes occur by which external exchange of L occurs with added free ligand. For X = n Bu and L = THF, the activation parameters for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…[Ph 3 C + ][B(C 6 F 5 ) 4 − ] (Boulder Scientific) was used as received. [CH[C(Me)N‐DIPP] 2 Mg n Bu] 2 [( Me BDI)Mg n Bu] 2 , [45] and CH[C(tBu)N‐DIPP] 2 Mg n Bu ( t Bu BDI)Mg n Bu [45] were synthesized according to literature procedures. [( Me BDI)Mg + ][B(C 6 F 5 ) 4 − ] was synthesized according to an adapted literature procedure by using [( Me BDI)Mg n Bu] 2 instead of [( Me BDI)Mg n Pr] 2 [27] .…”
Section: Methodsmentioning
confidence: 99%
“…[Ph 3 C + ][B(C 6 F 5 ) 4 − ] (Boulder Scientific) was used as received. [CH[C(Me)N‐DIPP] 2 Mg n Bu] 2 [( Me BDI)Mg n Bu] 2 , [45] and CH[C(tBu)N‐DIPP] 2 Mg n Bu ( t Bu BDI)Mg n Bu [45] were synthesized according to literature procedures. [( Me BDI)Mg + ][B(C 6 F 5 ) 4 − ] was synthesized according to an adapted literature procedure by using [( Me BDI)Mg n Bu] 2 instead of [( Me BDI)Mg n Pr] 2 [27] .…”
Section: Methodsmentioning
confidence: 99%
“…Three-coordinated Mg complexes with terminal nBu-groups are rare and are best described for the β-diketiminate class of ligand that allows some comparison with the sterics of HL − . Comparable monomeric complexes of [{HC(RCNAr) 2 }MgnBu] with an overall molecular structure similar to 1 were found for R = Me and Ar = 2,6-(Ph 2 CH) 2 -4-MeC 6 H 2 (≡ Ar*) [27], and R = tBu and Ar = Dip [28]. For the respective complex with R = Me and Ar = Dip [29] and smaller β-diketiminates, molecular structures with bridging nBu groups and four-coordinate Mg centres were found.…”
Section: Resultsmentioning
confidence: 91%
“…For the respective complex with R = Me and Ar = Dip [29] and smaller β-diketiminates, molecular structures with bridging nBu groups and four-coordinate Mg centres were found. Thus, the steric profile of HL − , at least when coordinated to Mg, can be approximately compared with [{HC(tBuCNDip) 2 were found for R = Me and Ar = 2,6-(Ph2CH)2-4-MeC6H2 (≡ Ar*) [27], and R = tBu and Ar = Dip [28]. For the respective complex with R = Me and Ar = Dip [29] In analogy to the synthesis of a sterically less hindered methanediide Mg complex of type B (M = Mg, E = NSiMe3) [16], which was synthesized at 140 °C using MgnBu2, we heated [HLMgnBu] 1 to various high temperatures (up to 200 °C) though only obtained a complex product mixture were found for R = Me and Ar = 2,6-(Ph2CH)2-4-MeC6H2 (≡ Ar*) [27], and R = tBu and Ar = Dip [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of methyl-and nbutyl magnesium b-diketiminate derivatives have been reported, all prior syntheses of these compounds have been dependent upon either deprotonation of the diimine ligand precursor with a diorganomagnesium or salt metathesis between the lithiated b-diketiminate and a Grignard reagent. [57][58][59][60][61][62][63][64][65][66] The successful synthesis of compound 6 prompted extension of this reactivity to several further terminal alkenes (Scheme 3). Although reaction of 1-octene at 80 C also proceeded to completion within an analogous 4 hour time period to provide the magnesium n-octyl complex (7), similar thermal treatment of both 3-phenyl-1-propene and 3,3-dimethyl-1-butene indicated that the facility of these C]C insertion reactions is signicantly perturbed by the relative steric demands of the alkene substrate.…”
Section: Stoichiometric Reactions Of Compound 4 With Alkenesmentioning
confidence: 99%